Factors Affecting the Income of Milkfish Farmers During the Covid-19 Pandemic in Napalakura Village, Napabalano Sub District, Muna District - Sitti Zulma; Muhammad Aswar Limi; La Ode Kasno Arif (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
This study aims to identify the characteristics of milkfish pond farming, assess the income of milkfish pond farmers, and determine the factors affecting the income of milkfish pond farmers in Napalakura Village, Napabalano District, Muna Regency, in the context of the Covid-19 pandemic. The investigation was conducted from August to December 2021 in Napalakura Village, Napabalano District, Muna Regency. Using a census sampling technique, forty respondents were selected for the study. A descriptive quantitative approach was employed for data analysis, providing insights into aquaculture characteristics, income analysis, and multiple linear regression analysis. The study findings revealed that milkfish farming encompasses breeding, fertilizing, maintaining, and harvesting. Milkfish farmers reported IDR 6,368,489 per cycle, equating to IDR 1,512,125 per month. With a 95% confidence level (α = 0.05), the variables of production and labor were found to have a positive and significant impact on the income of milkfish farmers. At the same time, land area and capital investment showed no significant effect on the farmers' income.